Design of realistic mathematics-based student worksheets to improve students’ critical thinking ability - Suparman, Suparman; Wijayanti, Dita Dwigus (Asian Journal of Assessment in Teaching and Learning, 2019)
Critical thinking ability is one of the abilities that must be possessed by students in the 2013 curriculum learning. Worksheets Students who have not integrated critical thinking skills will hinder learning objectives. The Indonesian Realistic Mathematics Approach is one approach that can be used by teachers to be able to improve students’ critical thinking. This study aims to design worksheets of students who use the Indonesian Realistic Mathematics Approach to improve critical thinking skills and to produce the design of mathematics student worksheets with a realistic mathematical approach for students of class X Vocational High School. This research applied the ADDIE development model research, which consists of four stages: Analysis, Forming, Developing, Implementing and Evaluating. It focuses on the product planning stage of the students’ worksheet. Two schools were involved in this study were YPKK 3 vocational school Sleman Yogyakarta and Budi Mulia 2 vocational school Yogyakarta. A questionnaire was administrated to the respondents of this study. The results showed that the material feasibility test with an average score of 89. Thus, the design of student worksheets with realistic mathematical approach is promising.